An evaluation of a provider-initiated HIV testing and counselling (PITC) intervention for patients with sexually transmitted infections in Cape Town, South Africa - Leon, Natalie H (Department of Public Health and Family Medicine, 2015)
The objectives of the study were to assess the impact of a PITC intervention on HIV test uptake rates and on access to HIV care, to evaluate the extent to which ethical principles were upheld in its implementation, and to examine the influence of implementation factors on the intervention.